2014
DOI: 10.9790/2402-08735867
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of heavy metal accumulation and antioxidant responses in Jatropha curcas L

Abstract: Jatropha curcas L. commonly known as physic nut or purging nut, is a drought resistant shrub belonging to the family Euphorbiaceae, was analyzed for its accumulation capacity of heavy metals such as lead (Pb), cadmium (Cd) and chromium (Cr). Bioassay was conducted by raising the plant by vegetative propagating the stem cutting in varying concentration of respective heavy metals. The metal concentration in the bioparts of experimental plant revealed that the treated plants accumulated enormous quantity of lead,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
1
0
1
Order By: Relevance
“…Alternanthera tenella Colla (Amaranthaceae) is a fast-growing, invasive alien herb widely found in India, especially in polluted areas such as industrial zones. A. tenella is a facultative metallophyte and has already been proven as a bioaccumulator of Cd under controlled micro-conditions (Rodrigues et al 2017) and also showed responses to various HM stress (Chinmayee et al 2014). However, additional studies with this species can also verify its potential use as a bioindicator and phytoremediator in areas contaminated by these heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…Alternanthera tenella Colla (Amaranthaceae) is a fast-growing, invasive alien herb widely found in India, especially in polluted areas such as industrial zones. A. tenella is a facultative metallophyte and has already been proven as a bioaccumulator of Cd under controlled micro-conditions (Rodrigues et al 2017) and also showed responses to various HM stress (Chinmayee et al 2014). However, additional studies with this species can also verify its potential use as a bioindicator and phytoremediator in areas contaminated by these heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…El estudio reveló disminución de actividad de CAT y PAL en L. hexandra en la mayor dosis de HTP (90 g kg -1 ), similar efecto para CAT fue reportado porAchuba (2014) en Vigna unguiculata y Zea mays expuesta a queroseno, yRusin et al (2018) en Triticum aestivum L expuestas a aceite de motor y diésel. La respuesta en PAL fue similar a lo reportado porChinmayee et al (2014) en Jatropha curcas L. y JaEczak-Pieni}ek et al…”
unclassified